Medial and dorsal lateral septum involving social disruption stress-primed escalation in acid-induced writhes - Liao, Yi-Han; Sun, Li-Han; Su, Yi-Chi; Yao, Wei-Jen; Yu, Lung (Frontiers in Molecular Neuroscience, 2023)
Introduction Stress may cause prospective escalations in abdominal pain magnitude and accumbal TRPV1 expression, while central neural circuits mediating these stress effects remain unclear. Methods Using retrograde tracing methods, we first demonstrated the existence of a medial septal-dorsal lateral septal -accumbal circuit very likely involving social disruption stress-primed escalations in acid-induced writhes and accumbal TRPV1 level. An intersectional viral strategy and virus-carrying hM3Dq and hM4Di DREADDs were, then, employed to selectively modulate GABAergic and cholinergic neuronal activity in medial and dorsal lateral septum. Results Exciting medial septal GABAergic neuron was found to prevent social disruption stress-primed escalations in acid-induced writhes and accumbal TRPV1 and PKCε expressions. Likewise, inactivating dorsal lateral septal cholinergic neurons was also effective in abolishing these stress-primed escalations. Inactivating GABAergic neuron in non-stressed animals’ medial septum was found to reproduce the stress-primed effects in causing heightened acid-induced writhes and accumbal TRPV1 and PKCε levels. Discussion These results, taken together, prompt us to conclude that social disruption stress may produce plastic changes in a newly-identified medial septal-dorsal lateral septal-accumbal circuit. Moreover, medial septal GABAergic hypoactivity and dorsal lateral septal cholinergic hyperactivity are, at least, two likely causes reflecting such stress-produced escalations in abdominal pain magnitude and pain transduction-related protein over-expression in nucleus accumbens.